ETF Activity and Informational Efficiency of Underlying Securities - Glosten, Lawrence; Nallareddy, Suresh; Zou, Yuan (Management Science, 2021)
This paper investigates the effect of exchange-traded funds’ (ETFs’) activity on the short-run informational efficiency of their underlying securities. We find that ETF activity increases short-run informational efficiency for stocks with weak information environments. The increase in informational efficiency results from the timely incorporation of systematic earnings information. In contrast, we find no such effect for stocks with stronger information environments. ETF activity increases return comovement, and this increase is partly attributable to the timely incorporation of systematic earnings information. Further, ETF activity is associated with an attenuation of postearnings-announcement drift and an increase in active share lending. This paper was accepted by Suraj Srinivasan, accounting.